Corporate social responsibility reporting: meeting stakeholders expectations or efficient allocation of resources? - Rashid, Afzalur (International journal of accounting and information management, 2021)
Purpose This study aims to examine whether corporate social responsibility (CSR) reporting adds any value to the firm. Design/methodology/approach This study uses content analysis to capture the specific CSR-related attributes and to construct a CSR reporting index. The data is manually collected from 115 publicly listed firms on the Dhaka Stock Exchange. The companies audited financial statements were the source of data. This study uses an ordinary least square regression analysis to examine the relationship between CSR reporting and firm performance. Findings The results of this study show that firms’ involvement in CSR activities and related reporting has a significant positive influence on firm performance only under an accounting-based performance measure. However, firms’ involvement in CSR activities and related reporting has a significant negative influence on firm performance under a market-based performance measure. Research limitations/implications This study is subject to some limitations, such as the subjectivity or judgement associated in the coding process. Practical implications The findings of this study imply that firms may be involved in CSR reporting to meet the stakeholders’ expectations, CSR reporting does not necessarily increase the intrinsic value of the firm. Originality/value This study supports the stakeholder theory and contributes to the literature on the practices of CSR reporting in the context of developing countries.